Nucleotide sugar biosynthesis occurs in the glycosomes of procyclic and bloodstream form Trypanosoma brucei. - Maria Lucia Sampaio Guther; Alan R Prescott; Sabine Kuettel; Michele Tinti; Michael A J Ferguson (PLoS Neglected Tropical Diseases)
In Trypanosoma brucei, there are fourteen enzymatic biotransformations that collectively convert glucose into five essential nucleotide sugars: UDP-Glc, UDP-Gal, UDP-GlcNAc, GDP-Man and GDP-Fuc. These biotransformations are catalyzed by thirteen discrete enzymes, five of which possess putative peroxisome targeting sequences. Published experimental analyses using immunofluorescence microscopy and/or digitonin latency and/or subcellular fractionation and/or organelle proteomics have localized eight and six of these enzymes to the glycosomes of bloodstream form and procyclic form T. brucei, respectively. Here we increase these glycosome localizations to eleven in both lifecycle stages while noting that one, phospho-N-acetylglucosamine mutase, also localizes to the cytoplasm. In the course of these studies, the heterogeneity of glycosome contents was also noted. These data suggest that, unlike other eukaryotes, all of nucleotide sugar biosynthesis in T. brucei is compartmentalized to the glycosomes in both lifecycle stages. The implications are discussed.